EFEKTIVITAS PEMBERIAN DAUN KELOR TERHADAP PENINGKATAN PRODUKSI ASI IBU NIFAS DI DESA TAMANSARI KECAMATAN MUMBULSARI KABUPATEN JEMBER: The Effectiveness Of Providing Moringa Leaves In Increasing Breast Milk Production For Public Mothers In Tamansari Village, Mumbulsari District, Jember District - Trisna Pangestuning, Tyas; Perbawati, Dinar (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2024)
Breastfeeding is a natural process, but often mothers do not manage to exclusively breastfeed or stop breastfeeding early. Lactation preparations play an important role in the success of breastfeeding in infants. It should be prepared from the end of pregnancy, and the lactation process begins as soon as the baby is born in the process of Early Initiation of Breastfeeding. The efforts of health workers in increasing breastfeeding coverage have not been able to meet the achievement of the targets that have been set, because not all mothers breastfeed their babies for various reasons. Among them are concerns about the adequacy of the amount of breast milk for the baby. The purpose of this study was to analyze the effectiveness of Moringa leaf administration on increasing breast milk production in postpartum mothers. In this study, researchers used a pre-experimental research design with a pretest and posttest research design without a control group (Pretest day Postest Without Control Group). Example of pairet t test results with a value of P-value = 0.000 (p < 0.05 so that there is a significant influence on the effectiveness of Moringa leaf giving to increase breast milk production for postpartum mothers. By consuming Moringa leaves regularly every day